Comparative evaluation of shear bond strength of composite resin bonded to acid etched or Nd:Yag lased enamel - Mridula Goswami; Asha Singh (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2011)
Aims: In vitro evaluation of the shear bond strength of composite resin bonded to enamel which is pretreated using acid etchant or pulsed Nd:YAG. Qualitative morphological changes in enamel surfaces were observed under a scanning electron microscope (SEM). Materials and Methods: 60 extracted human teeth were divided in two groups of 30 each (Groups A and B). In Group A, prepared surface of enamel was etched using 35% phosphoric acid (Scotchbond, 3M). In Group B, enamel was surface treated by a surgical Nd:YAG laser beam (Medilas 4060 Fibertom) at 0.8 W, 10 Hz, for 10 s with 80 mJ/pulse power. Bonding agent (single bond dental adhesive, 3M) was applied over the test areas on 20 samples of Groups A and B each, and light cured. Composite resin (Z 100, 3M) was applied onto the test areas as a 3 mm diameter cylinder, and light cured. The samples were tested for shear bond strength. Remaining 10 samples from each group were observed under SEM for morphological changes. Results: The mean shear bond strength was 20.00 MPa (΁ 1.93) and 13.28 MPa (΁1.97) for Group A and B, respectively. The difference in mean values was statistically significant between Groups A and B (P<0.001). Under SEM, Group A showed typical honeycomb appearance and Group B showed bubble-like cavities. Conclusions: In enamel, acid etch technique showed higher shear bond strength.